Prevention of dietary fat-fueled ketogenesis attenuates BRAF V600E tumor growth - Xia, Siyuan (Cell Metab, 2017)
Lifestyle factors including diet play an important role in the survival of cancer patients. However, the molecular mechanisms underlying pathogenic links between diet and particular oncogenic mutations in human cancers remain unclear. We recently reported that the ketone body acetoacetate selectively enhances BRAF V600E mutant-dependent MEK1 activation in human cancers. Here we show that a high-fat ketogenic diet increased serum levels of acetoacetate, leading to enhanced tumor growth potential of BRAF V600E-expressing human melanoma cells in xenograft mice. Treatment with hypolipidemic agents to lower circulating acetoacetate levels or an inhibitory homologue of acetoacetate, dehydroacetic acid, to antagonize acetoacetate-BRAF V600E binding attenuated BRAF V600E tumor growth. These findings reveal a signaling basis underlying a pathogenic role of dietary fat in BRAF V600E-expressing melanoma, providing insights into the design of conceptualized “precision diets” that may prevent or delay tumor progression based on an individual’s specific oncogenic mutation profile.